Particle-size fractions-dependent extracellular enzyme activity in sediments and implications for resource allocation in a subtropical mangrove ecosystem - L. Luo; J.-D. Gu (Global Journal of Environmental Science and Management)
The distribution of extracellular enzyme activities in particle-size fractions of sediments was investigated in a subtropical mangrove ecosystem. Five enzymes involved in carbon (C), nitrogen (N), and phosphorus (P) cycling were analyzed in the sand, silt, and clay of sediments. Among these fractions, the highest activities of phenol oxidase (PHO), β-D glucosidase (GLU), and N-acetyl-glucosiminidase (NAG) were found in sand, and greater than bulk sediments of both intertidal zone (IZ) and mangrove forest (MG). This result implied that sand fractions might protect selective enzymes through the adsorption without affecting their activities. Additionally, the enzyme-based resource allocation in various particle-size fractions demonstrated that nutirents availability varied with different particle-size fractions and only sand fraction of MG with highest total C showed high N and P availability among fractions. Besides, the analysis between elemental contents and enzymes activities in particle-size fractions suggested that enzymes could monitor the changes of nutrients availability and be good indicators of ecosystem responses to environmental changes. Thus, these results provided a means to assess the availability of different nutrients (C, N, and P) during decomposition of sediment organic matter (SOM), and thus helping to better manage the subtropical mangrove ecosystems to sequester C into SOM.